Light-dark O2 dynamics in submerged leaves of C3 and C4 halophytes under increased dissolved CO2: clues for saltmarsh response to climate change - Duarte, B. (2017)
Waterlogging and submergence are the major constraints to which wetland plants are subjected, with inevitable impacts on their physiology and productivity. Global warming and climate change, as driving forces of sea level rise, tend to increase such submersion periods and also modify the carbonate chemistry of the water column due to the increased concentration of CO2 in the atmosphere. In the present work, the underwater O2 fluxes in the leaves of two abundant Mediterranean halophytes were evaluated at different levels of dissolved CO2. Photosynthetic enhancement due to increased dissolved CO2 was confirmed for both Halimione portulacoides and Spartina maritima, probably due to high tissue porosity, formation of leaf gas films and reduction of the oxygenase activity of Rubisco. Enhancement of the photosynthetic rates in H. portulacoides and S. maritima was concomitant with an increase in energy trapping and transfer, mostly due to enhancement of the carboxylation reaction of Rubisco, leading to a reduction of the energy costs for carbon fixation. Transposing these findings to the ecosystem, and assuming increased dissolved CO2 concentration scenarios, the halophyte community displays a new ecosystem function, increasing the water column oxygenation and thus reinforcing their role as principal primary producers of the estuarine system.